Manajemen Keuangan Sekolah di MI Darul Hikmah Entalsewu Sidoarjo - Dina Puspita Ningsih; Ahmad Hariyadi (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
This study aims to analyze the financial management at Madrasah Ibtidaiyah (MI) Darul Hikmah Entalsewu. The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the financial management at MI Darul Hikmah Entalsewu is car ied out through three main stages, namely planning, implementation, and evaluation. At the planning stage, the madrasah comprehensively prepares the financial budget by involving stakeholders. The main source of funding comes from the government's School Operational Assistance (BOS) funds and voluntary contributions/donations from students. In the implementation stage, the madrasah meticulously records each receipt and expenditure of funds, then allocates the funds according to the operational needs of the madrasah and the needs of the students. Furthermore, in the evaluation stage, internal parties (the principal and the foundation) as well as external parties (the Ministry of Religious Affairs) are involved in the supervision, monitoring, and accountability of the use of funds. Through this comprehensive financial management process, the financial management at MI Darul Hikmah Entalsewu is car ied out in a transparent, accountable, and compliant manner with the applicable regulations. The findings of this research can be a reference for other madrasahs in implementing effective financial management.